REVIEW OF COVID-19 AND AUDIO-VESTIBULAR SYMPTOMS: WHAT WE KNOW SO FAR? - Bukurov, Bojana (HEALTH CARE, 2022)
Introduction/Aim: Although we have already entered the third year of the pandemic, the pathophysiological mechanisms of Severe Acute Respiratory Syndrome Corona Virus 2 (SARS-CoV-2) infection are still not fully elucidated. While symptoms of smell and taste dysfunction have been associated with this infection from the beginning, not much has been reported on other sensory systems, in the first place the hearing and balance. The aim of this review paper is to summarize data from the literature and the latest publications and answer the question whether there is a causal link between COVID-19 and inner ear damage. Methods: This review paper presents the latest data and evidence obtained from search of PubMed database by keywords: COVID-19, hearing loss, tinnitus and vertigo. The search identified more than 460 publications. After reviewing the title and abstract, most papers were excluded due to non-compliance with the eligibility criteria. Results: A total of 16 papers fulfilled the eligibility criteria and were reviewed in their entirety. The results of the meta-analysis indicated that the incidence of hearing loss was 3.1% (Confidence Interval - CI: 0.01-0.09), of tinnitus 4.5% (CI: 0.012-0.153), and dizziness 12.2% (CI: 0.070-0.204). Conclusion: Most published papers are characterized by limitations and high risk of bias (no control arm, missing data, and no reference to confounding factors). For now, no certain causal relationship between this infection and damage to the senses of hearing and the sense of balance can be established.